Edukasi Menanggulangi Pandemi Covid-19 Berbasis Komuniti untuk Mewujudkan Kekuatan Pentahelix - Adhani, Lisa; Saing, Bungaran; Widodo, Hernowo; Setiawati, Siti; Ismaniah (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
The theme of this PKM is Education to Overcome the Pandemic Covid-19 Community- Based to Realize the Power of Pentahelix in the midst of society. Overcoming the community-based Covid-19 pandemic is a major concern at this time, where local people are empowered to form community that will become agents of change in the communities in overcoming Covid-19, breaking the chain of transmission as well as monitoring the implementation of the new normal life era. The Pentahelix is a method of optimizing the 5 (five) strengths (Government, community (society), academics, entrepreneurs and social media) that the government is currently developing as an effort to accelerate the handling of covid-19. Education is carried out by providing assistance to form communities in Kampung Karang Mulya, Desa Karang Satria, Tambun, Bekasi, that implement strategic policies in handling Covid-19 through the formation of young satgas post.